'FAST positive' reversal & pneumoperitoneum: A novel sign of traumatic bladder rupture. (July 2021) - Chennatt, Jaine J; Rattan, Amulya; Dhiman, Ajay K
Urinary bladder injuries are uncommon, accounting for just 1.6% of all abdominal trauma. The most common presenting symptoms are hematuria, abdominal pain and inability to void. Ascites is the most typical manifestation on CT. We hereby report a case of a 24-year-old male victim of a road traffic injury with an unusual presentation of pneumoperitoneum and "reversal" of FAST positive status as the presenting signs of bladder injury. Prior awareness of urinary bladder injury as the etiology of pneumoperitoneum can possibly decrease morbidity with consideration of minimal access surgery for management. Compared to pneumoperitoneum, "FAST reversal" in catheterized patients is quite peculiar and sufficiently specific per se to warrant a cystogram or thorough intraoperative bladder evaluation.